The Qur’anic divine guidance and its civilizational impact, a study on Surat Al-Alaq - Mohamed Sayed Emam, Amr; Abu Hassan, Muhammad Ikram (Human Resource Management Academic Research Society, 2024)
The Holy Qur’an is an inexhaustible wellspring and is the Holy Book that contains the Sharia law secrets, and within it lies the cultural formation secret of Muslims. Indeed, our nation, in this era, is in dire need of extrapolating this book to extract its divine guidance and apply it in its contemporary reality. In this study, we are attempting to explore some of this divine guidance through the first surah revealed to the Messenger of Allah -May Allah bless him and grant him peace- which is Surat Al-Alaq (“Iqraa” Read); whereas the one, who meditates and contemplates this blessed Surah, will find within it commanded several divine guidance, which are: knowledge, learning, reading, fear of Allah; as well as verification by closeness means to Him, Glory be to Him. However, there are obstacles to guidance that Allah warned us about in this Surah, which are: tyranny, heedlessness of Allah by forgetting to return to Him, and clinging to something other than Him. Hence, this research is a serious attempt to re-recite the Holy Qur’an and search for its divine guidance, which means contemplating its words and meanings, and this achieves the ultimate objective of this honorable book, which is light and mercy for those who believe in it and for others as well.